Emergence and assessment of interpersonal experience and behavior in a nonverbal, generative, game-like paradigm - Stefan Westermann; Arne Sibilis (Acta Psychologica, 2022)
Dominance, hostility and autonomy are interpersonal phenomena that emerge from the complex dyadic interplay of two individuals reciprocally influencing each other. Assessing the complexity of interpersonal interactions usually involves its reduction, for example with self-report and observer-rated measures informed by the structural analysis of social behavior (SASB). In contrast, letting individuals generate a complex stream of interpersonal experience and behavior from moment to moment is an empirical approach not yet usual in interpersonal theory. In the present study, we developed and evaluated an interpersonal, generative paradigm that allows participants to interact nonverbally and spontaneously with a computer-controlled other player in real-time without the need for introspection or the capacity to verbalize potentially implicit interpersonal processes. In the game-like paradigm, participants use the keyboard to take over objects such as a handcar to move autonomously around and encounter interfering or freedom granting artificial other players. We expected that participants (1) experience the nonverbal so-called game mechanics of the paradigm as interpersonal in nature, (2) behave towards the other players in an interpersonally complementary way, and (3) are influenced by their own trait interpersonal expectations. During the paradigm, 40 participants appraised the majority of the game mechanics and computer-controlled other players as intended. Also, interpersonal traits affected the spontaneous behavior towards artificial characters. These findings corroborate the feasibility and validity of a generative assessment of interpersonal dynamics beyond self-reports and observer ratings. The paradigm paves the way for the empirical testing of formal, computational models of dyadic interaction.